How do we sell the hygiene message? With dollars, dong or excreta? - West Line; Phuc Pham; Jensen Peter (BMC, 2010)
Abstract In North and Central Vietnam it is common among farmers to use excreta from the family double vault composting latrine (DVC) as fertilizer in the fields. The official Vietnamese health guidelines stipulate a six-month period of composting before applying excreta to two of their three annual crops. However, farmers in this region cannot afford to follow these guidelines and this paper presents the reasons why. In their efforts to ensure optimal hygienic conditions, by providing a guideline, the Vietnamese health authorities have not put sufficient attention to the 'excreta economy' in relation to farmers' livelihoods. The free fertilizer in the household DVC represents a value of approximately US$ 15.5 per year - or the equivalent of 15 percent of the annual household income for the poorest 20 percent of farmers. For this reason, the economic benefits derived from free fertilizer outweigh the hygiene message for most Vietnamese farmers. Even at national level the excreta economy has an impact. If Vietnam were to replace human excreta with imported fertilizer, it would involve an extra national expenditure of at least US$ 83 million a year. In order to convince Vietnamese farmers to adopt different fertilizing methods when reusing human excreta, it is necessary for the Vietnamese health authorities to change their hygiene message. They need to replace their current health sector-specific approach with a holistic one that takes the premises of farmers' livelihoods into account. If they do not the hygiene message will simply be lost.